Pemanfaatan Web Berbasis Aplikasi Multimedia Pada Mata Kuliah Dasar-Dasar Jurnalistik - Fifit Fitriansyah (Universitas Bina Sarana Informatika, 2017)
Learning process is the most important activity. Therefore, the successful achievement of learning objectives depends on how effectively the learning process takes place. Effective learning process can’t be separated from the role of learning resources that are used, in which the utilization and the selection of appropriate learning resources greatly affects the learning process. Therefore, an aspect of learning resources support the success of the learning process. Thus, use of learning resources in the form of web-based multimedia applications in basic journalism courses will increase effectiveness in learning, so that learning becomes more meaningful to the students to gain direct experience in virtual reality.